Effect of Exserohilum monoceras (Drechslera) leonard & suggs on the competitiveness of Echinocloa cruss-galli (L.) P. Beauv - Kadir, Jugah; Sajili, Mohammad Hailmi; Juraimi, Abdul Shukor; Napis, Suhaimi (Universiti Putra Malaysia Press, 2008)
The use of bioherbicide to reduce interference by barnyard grass in rice cropping system has been suggested but has not been reported. Against this conceptual background, a mini-plot study was conducted to simulate the efficacy of Exserohilum monoceras to reduce competitiveness of barnyard grass in rice using replacement series experiment. The effect of E. monoceras on rice was negligible, as it did not cause any infection. Severe infection was observed on barnyard grass inoculated with this fungus at all plant densities as indicated by high AUDPC values (ranges from 610.35-468.28 unit2) and fast disease progress rates (r L= 0.48 logit/day). Rice biomass in mixture with diseased weed was higher than in the presence of healthy weed, and is not significantly different from rice biomass in the non-weedy control. In the inoculated experiment, at lower weed density, competition between barnyard grass and rice was not apparent despite the fact that the weed growth was reduced. As the weed density increased, rice continued to grow, but barnyard grass was suppressed; the growth difference was bigger and more measureable. In the non-inoculated control, the interaction between barnyard grass and rice was observed at 2:2 ratio, but at 3:1 in the inoculated experiment, indicating that rice was more competitive over barnyard grass. It took three barnyard grass to equal the shoot dry weight of one rice plant. This study provides strong evidence of the ability of E. monoceras in reducing the competitive ability of barnyard grass and thus provides new opportunities for the future of biological weed control in Malaysia.